The association between financial and non-financial incentives and performance of posyandu cadres - Asrianah Asrianah; Ratih Wirapuspita Wisnuwardani; Iriyani Iriyani; Nastitie Cintiya Nurzihan; Muhammad Nuzul Azhim Ash Siddiq; Triana Fitriastuti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Penajam Paser Utara was the first district to provide cash incentives to Posyandu cadres for infants and toddlers and was the district with the largest incentive in 2010 at IDR 200,000 per month. However, the provision of incentives was uneven. However, there are still differences in the amount of cash incentives received by cadres. This study aims to determine whether there is a relationship between incentives and the performance of Posyandu cadres in Penajam Paser Utara District. This type of research was quantitative, using a correlational analysis method and a cross-sectional approach with a sample size of 303 respondents. The research was conducted in the Posyandu working area in the Penajam Paser Utara Regency between November and December 2023. Data were collected online using a Google form link provided to respondents via WhatsApp. Data were analyzed using the chi-squared test. The results showed that 251 cadres (82,8%) performed satisfactorily, Three types of non-cash incentives were associated with performance: health benefits, uniforms, and neighborhood support (p-value <0,05). This study concludes that there is a positive relationship between cash and non-cash incentives on cadr e performance in the Penajam Paser Utara Region (p < 0,001).